Development of a remote tending system for analog broadcast transmitters - Gerino Mappatao; Isaiah Mari Zebedia Bautista; Marc Kevin Orsos; Mark Aldrine Ribo; Joseph Castillo (Institute of Advanced Engineering and Science, 2019)
Whenever a broadcast transmitter is on-air, it is required to be tended by licensed broadcast technicians. Technicians periodically monitor the transmitter performance, record the supply voltage and current at the last stage of the power amplifier and keeps a copy for at least two years. Also recorded are the times the transmitter is turned ON and OFF as well as the times the transmitter shuts down and returns back to air. This paper proposes a system to remotely tend analog transmitters in one central monitoring station. The remote tending of several transmitters in one location is made possible through internet connection. However, the challenge in the proposed system is in the gathering of transmitter data. A prototype of the system was constructed and tested in an FM broadcast transmitter. Test results on the prototype performance show that the proposed system can effectively be used to remotely monitor, record data and control the status of analog broadcast transmitters. The primary feature of the proposed system of monitoring several transmitters in one location will bring cost effective advantages to the broadcast operators.